Characterization of freezing effect upon stability of, probiotic loaded, calcium-alginate microparticles - Sousa, Sérgio
tMicroencapsulation, utilizing different techniques and polymers, has been studied with the objective of maintainingprobiotic viability in food matrices, protecting the cells from their detrimental environment, storage conditions andthe passage of gastrointestinal tract (GIT). The main objective of this study was to assess the effect of freezing at−20◦C upon probiotic alginate-calcium microparticles’ integrity and functionality through parameters such as size,morphology and structure of microparticles as well as to assess cell resistance to simulated gastrointestinal tractconditions upon storage. In order to study the effect of freezing upon the stability of the microparticles, calcium-alginate microparticles, with or without probiotic cells (Lactobacillus casei-01, Lactobacillus paracasei L26, Lactobacillusacidophilus KI and Bifidobacterium animalis BB-12), were characterized at production time and after 60 days storage at−20◦C. An increase in particle size, loss of the spherical shape and porous net damages were observed after 60 daysof storage at −20◦C. In accordance, encapsulation in alginate was not able to exert protection to the encapsulatedprobiotic cells stored at −20◦C for 60 days, especially from acid and particularly bile salts. B. animalis BB-12 revealedto be the most resistant probiotic strain, to both the microencapsulation process and to GIT simulated conditions.